Gambaran Subjective Well Being Mahasiswa Kedokteran Kota Bandung - Disa Aurea Annisa Nureffa; Andhita Nurul Khasanah (UNISBA Press, 2022)
Abstract. The existence of the COVID-19 pandemic phenomenon has increased the need for medical personnel, the number of doctors, so that medical faculty students are urgently needed. The stressors faced by medical students come from academic and non-academic so that medical students have extraordinary challenges in their lives and affect their subjective well being. However, the COVID-19 pandemic has also made medical faculty students better prepare themselves before entering society. The research was conducted to determine the SWB of Medical Faculty students in Bandung City. Measuring tools used. Positive Affect and Negative Affect Scales developed by Watson. Clark. and Tellegen and Diener's Life Satisfaction scale adapted by Hanif Akhtar. Respondents were students of the medical faculty of Bandung City, amounting to 332 people. The study used a convenience sampling technique. The data analysis technique used descriptive analysis. The results showed that overall medical students showed high subjective well being as many as 182 people (55%) and classified as having low subjective well being as many as 150 people (45%). Based on gender, women had lower SWB (M=64.58) than men (M=68.84). Based on age, 17 years old had low SWB (M=61.25) compared to 23 years old with high SWB (M=73.64). Based on the level, level 1 students have lower SWB (M=64.10) while level 3 students have high SWB (M=68.61). Abstrak. Adanya fenomena pandemi COVID-19 menjadikan meningkatnya kebutuhan akan tenaga medis, jumlah dokter, sehingga mahasiswa fakultas kedokteran sangat dibutuhkan. Penghayatan stressor yang dihadapi oleh mahasiswa fakultas kedokteran berasal dari akademik dan non akademik sehingga mahasiswa kedokteran memiliki tantangan yang luar biasa dalam kehidupannya dan mempengaruhi Subjective well being mereka. Namun pandemi COVID-19 juga membuat mahasiswa fakultas kedokteran lebih mempersiapkan diri sebelum terjun kedalam masyarakat. Penelitian yang dilakukan bertujuan untuk mengetahui SWB pada Mahasiswa Fakultas Kedokteran Kota Bandung. Alat ukur yang digunakan. Positive Affect and Negative Affect Scales yang dikembangkan oleh Watson. Clark. dan Tellegen dan skala kepuasan hidup (Life Satisfaction) yang dibuat oleh Diener yang diadaptasi oleh Hanif Akhtar. Responden adalah mahasiswa fakultas kedokteran Kota Bandung yang berjumlah 332 orang. Penelitian menggunakan teknik convenience sampling. Teknik analisis data menggunakan analisis deskriptif. Hasil penelitian menunjukan secara keseluruhan mahasiswa fakultas kedokteran menunjukan Subjective well being yang tinggi sebanyak 182 orang (55%) dan tergolong memiliki subjective well being rendah sebanyak 150 orang (45%). Berdasarkan jenis kelamin, perempuan memiliki SWB rendah (M=64.58) daripada laki-laki (M=68.84). Berdasarkan usia, 17 tahun memiliki SWB rendah (M=61.25) dibandingkan usia 23 tahun dengan SWB tinggi (M=73.64). Berdasarkan tingkat mahasiswa tingkat 1 memiliki SWB lebih rendah (M=64.10) sedangkan mahasiswa tingkat 3 memiliki SWB yang tinggi (M=68.61).